Proliferative Diabetic Retinopathy Detection Using Machine Learning - Tamboli, Neha; Malande, GS (International Journal of Computer Sciences and Engineering, 2020)
In this paper, the method for detection of neovascularization from fundus retinal image is presented. Neovascularization is the type of proliferative diabetic retinopathy and it is characterized by new, fragile retina vessels. It poses high risk for sudden vision loss. To avoid this risky situation, an early detection, proper treatment and diagnosis is essential. Therefore, we cannot underestimate the significance of accurate and timely detection of NV. We propose a method to detect NV which is based on automatic image processing that involves vessel segmentation using K-means, Vessel morphology, texture based features extraction and classification of images with support vector machine(SVM) and we achieved an average accuracy of 99 % on the selected test set.